Trends in the development of wireless laser energy transmission - Sokirkaiev, D.V.; Zarudny, A.A. (Radiotekhnika, 2025)
The article reviews and analyzes the current state of laser energy transfer (LET) systems and their development prospects. The key components of the system, including laser emitters and high-performance optoelectronic converters (OCs), as well as the influence of the transmission medium on the system efficiency are considered. Particular attention is paid to the optimization of each module of the OET to improve the efficiency of the entire system. The influence of laser radiation characteristics, DUT materials, temperature, and transmission conditions on the system efficiency is described. Modern achievements in the creation of multi-junction LETs using GaAs and other innovative materials are analyzed. Examples of practical applications of solar cells in aviation, space and military industries, including power supply of UAVs, spacecraft, as well as use in space solar power plants (SSPS) are considered. The main technical limitations of modern LPS systems, which hinder the increase in overall efficiency to the level of 20-25 %, are highlighted. Possible directions for further research, such as the improvement of materials, laser cooling systems, and the adaptation of the LPE design to specific operating conditions, are presented. LET is considered a promising technology that can change the approach to wireless energy supply in conditions where other methods are inefficient or dangerous. It is expected that in the future, due to further development of technologies, the efficiency of LEP systems will exceed 30%.